Dynamic Hippocampal CA2 Responses to Contextual Spatial Novelty - Bhasin, Guncha; Nair, Indrajith R. (Frontiers in Systems Neuroscience, 2022)
Hippocampal place cells are the functional units of spatial navigation and are present in all sub regions - CA1, CA2, CA3 and CA4. Recent studies on CA2 have indicated its role in social and contextual memory, but its contribution towards spatial novelty detection and encoding remains largely unknown. The current study aims to uncover how CA2 detects assimilates spatial novelty and to distinguish its functional role from CA1. Accordingly, a novel 3-day paradigm was designed where the animal was introduced to a completely new environment on the first day and on subsequent days, novel segments were inserted into the maze while other parts remained the same each say, allowing us to compare novel and familiar parts of the same track on multiple days. We found that spatial novelty lead to dynamic and complex hippocampal place cell firings, at both individual neuron and population level. Place cells in both CA1 and CA2 had strong responses to novel segments of the maze, leading to higher average firing rates and increased pairwise cross correlations across all 3 days. However, CA2 place cells that fired for novel areas had lower spatial information scores than CA1 place cells active in the same areas. At the ensemble level, CA1 only responded to spatial novelty on day 1, when the environment was completely novel, whereas CA2 responded to it on all days, each time novelty was introduced. Therefore, CA2 was more sensitive and responsive to novel spatial features even when introduced in a familiar environment, unlike in CA1.